2011
DOI: 10.1371/journal.pone.0016221
|View full text |Cite
|
Sign up to set email alerts
|

The Microbe-Derived Short Chain Fatty Acid Butyrate Targets miRNA-Dependent p21 Gene Expression in Human Colon Cancer

Abstract: Colonic microbiota ferment non-absorbed dietary fiber to produce prodigious amounts of short chain fatty acids (SCFAs) that benefit the host through a myriad of metabolic, trophic, and chemopreventative effects. The chemopreventative effects of the SCFA butyrate are, in part, mediated through induction of p21 gene expression. In this study, we assessed the role of microRNA(miRNA) in butyrate's induction of p21 expression. The expression profiles of miRNAs in HCT-116 cells and in human sporadic colon cancers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
155
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(164 citation statements)
references
References 32 publications
8
155
0
1
Order By: Relevance
“…A validated target gene of miR-106b is the cell cycle regulator p21. MiR-106b binds to the 3'UTR and inhibits the translation of p21 (Hu et al 2011). In the present study, butyrate and TSA were able to reduce miR106b expression in LT97 colon adenoma cells, especially after 48-h treatment and in HT29 cells (Supplementary Figure S1).…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…A validated target gene of miR-106b is the cell cycle regulator p21. MiR-106b binds to the 3'UTR and inhibits the translation of p21 (Hu et al 2011). In the present study, butyrate and TSA were able to reduce miR106b expression in LT97 colon adenoma cells, especially after 48-h treatment and in HT29 cells (Supplementary Figure S1).…”
Section: Discussionsupporting
confidence: 58%
“…Butyrate regulates the expression of genes and proteins involved in cell cycle control like p21 and Cyclin D1, leading to a cell cycle arrest in human colon cancer cells (Hamer et al 2008;Hinnebusch et al 2002;Siavoshian et al 2000). Lately, Hu et al (2011) as well as Humphreys et al (2013) showed that butyrate also influences miRNA expression in HCT116 and HT29 colon cancer cells, respectively. Therefore, it can act both via its function as HDI and by regulation of miRNA which are dysregulated in CRC (Bartley et al 2011;Schetter et al 2008;Slattery 2000;Wu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations